Exploring the direct and indirect effects of urban form on travel choices. The case of Athens, Greece. (13th April 2011) - Milakis, Dimitris
The article deals with the influence of land use on transportation. In studies up to the present, the relationship between the two has been regarded as an 'autonomous' system, an approach that has resulted in simplistic conclusions. The present study introduces non-urban form parameters, in pursuit of a two-fold goal: a) to compare the degree of influence of urban form and non-urban form parameters on travel behaviour; b) to identify the urban form parameters that directly influence transport choices. Data from the Metro Development Study has been employed for the area of Athens. The results indicate that urban form parameters influence public transport use and walking, the mean journey length and energy consumption by car, more than do non-urban form parameters. Non-urban form parameters influence mostly car use. The urban form parameters that turn out to influence transport choices directly are residential density and distance from city centre. Finally, conclusions about the strategic planning priorities that Athens could adopt in order for more sustainable travel patterns to appear are presented.